Immune responses in human CNS during rabies virus induced encephalitis - Franka, R.; Batten, B.; Shieh, W. J.; Niezgoda, M.; Zaki, S.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Understanding the mechanisms of rabies virus clearance from the CNS will be a significant step towards the treatment of clinical rabies. Although a few animal studies have provided insight about immune responses in the CNS during rabies encephalitis, data about the same are very scarce for humans. In our study, formalin-fixed, paraffinembedded, central nervous system (CNS) tissues from patients who succumbed to rabies following infection with RABV variants common to the tricolored bat (Perimyotis subflavus) in the United States, canine RABV present in Haiti, and canine RABV from Afghanistan, as well as tissues from a patient who recovered from clinical laboratory confirmed rabies following cat bite in Colombia, but succumbed as a result of secondary medical intervention, were subjected to comparative immunohistological evaluations identifying particular immune cell populations associated with rabies encephalitis. A non-encephalitic brain from an influenza patient was used as a negative control. Populations of B-cells (CD20), T-cells (CD3), and macrophages (CD68), as well as the presence of rabies virus antigens were compared using a semi-quantitative scale. In addition, gene expression analyses, using the Human Antiviral Response RT² Profiler™ PCR Array, focusing on the expression of 84 key genes involved in the innate antiviral immune response, were performed. No rabies virus antigens were detected in the brain tissue of the patient who survived clinical rabies or in the control brain. T-cells and macrophages were abundant in the parenchyma in all rabies patients, but B-cells were detected only in the perivascular tissue of the putative rabies survivor, and rabies patients infected with canine RABVs. Few T- and B- cells, and only local microglia cells, were detected in the influenza patient. Differences in the expression of multiple genes associated with innate immunity, as well as inflammatory responses, were identified, suggesting the importance of their role in rabies encephalitis and viral clearance from CNS tissue.